Targeting the Fibroblast Growth Factor Receptors for the Treatment of Cancer - Lemieux, Steven; Hadden, M. Kyle (Anti-Cancer Agents in Medicinal Chemistry, 2013)
Receptor tyrosine kinases (RTKs) are transmembrane proteins that play a critical role in stimulating signal transduction cascades to influence cell proliferation, growth, and differentiation and they have also been shown to promote angiogenesis when they are up-regulated or mutated. For this reason, their dysfunction has been implicated in the development of human cancer. Over the past decade, much attention has been devoted to developing inhibitors and antibodies against several classes of RTKs, including vascular endothelial growth factor receptors (VEGFRs), epidermal growth factor receptors (EGFRs), and platelet-derived growth factor receptors (PDGFRs). More recently, interest in the fibroblast growth factor receptor (FGFR) class of RTKs as a drug target for the treatment of cancer has emerged. Signaling through FGFRs is critical for normal cellular function and their dysregulation has been linked to various malignancies such as breast and prostate cancer. This review will focus on the current state of both small molecules and antibodies as FGFR inhibitors to provide insight into their development and future potential as anti-cancer agents.
Keywords: Pyrido[2; 3-d]pyrimidine